2005
DOI: 10.1007/s00227-004-1523-3
|View full text |Cite
|
Sign up to set email alerts
|

Zooid size parallels contemporaneous oxygen isotopes in a large colony of Pentapora foliacea (Bryozoa)

Abstract: The relationship between seasonal changes in temperature and the size of zooids within cheilostome bryozoans is explored by comparing zooid size and contemporaneous carbonate mineralogy within a single colony of a perennial species that grew in a highly seasonal environment. Previously published oxygen isotope profile data from two fronds of a large colony of Pentapora foliacea from the Irish Sea record the cyclical patterns related to seasonal changes in temperature experienced by the colony over 3 years of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…1). It is of utmost importance to adhere to strict criteria in data collection (O'Dea andOkamura 2000a, Okamura et al 2011). Thus, we measured the maximum lengths and widths of 20 randomly-selected autozooids per colony.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). It is of utmost importance to adhere to strict criteria in data collection (O'Dea andOkamura 2000a, Okamura et al 2011). Thus, we measured the maximum lengths and widths of 20 randomly-selected autozooids per colony.…”
Section: Methodsmentioning
confidence: 99%
“…For colonial animals like bryozoans, the relationship is expressed at the zooid level, and there is a reasonable body of evidence that zooid size is indeed inversely related to temperature. This evidence comes from diverse laboratory-reared material (e.g., Menon 1972, Hunter and Hughes 1994, Atkinson et al 2006, Amui-Vedel et al 2007, O'Dea et al 2007b, diverse field-collected material (e.g., Okamura 1987, O'Dea and Okamura 2000b, 2000c, O'Dea and Jackson 2002, O'Dea 2005, Lombardi et al 2006, and the growth of bryozoans in the field (O'Dea and Okamura 1999; see Okamura et al 2011 for further review) There are other factors that influence the ultimate size of zooids, the most obvious being species-specific colonial growth rules, such as the production of annual growth check lines (O'Dea andOkamura 2000b, O'Dea 2005, Okamura et al unpubl data), substrate irregularities, predation, and competition from other sessile encrusters, the influence of which can be minimized with the judicious rejection of randomly selected zooids as the approach requires (O'Dea andOkamura 2000a, O'Dea 2005). Salinity and food availability (Hageman et al 2009) have also been shown to influence zooid size, yet the effects are minimal in comparison with those of temperature (Okamura 1987, Hunter and Hughes 1994, O'Dea and Okamura 1999, 2000b, O'Dea 2005, O'Dea et al 2007b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in zooid size in modern day bryozoans is significantly related to the MART in which the colony grew due to the inverse relationship between zooid size and ambient temperature (Menon, 1972; Okamura, 1987; Okamura and Bishop, 1988;Hunter and Hughes, 1994;O'Dea and Okamura, 1999, 2000a, 2000b, 2000cO'Dea, 2005;Lombardi et al, 2006;Amui-Vedel et al, 2007). MART is estimated by measuring the amount of intracolony zooid size variation in fossil bryozoans and applying it to the following linear equation:…”
Section: Approach 1: Zooid-size Approach To Martmentioning
confidence: 99%
“…Records of planktonic primary productivity, in particular the bimodal spring and autumn phytoplankton blooms that characterise the Menai Straits and the Skagerrak (Pettersson 1991, Blight et al 1995, indicated that food availability could not have significantly affected zooid size. O'Dea (2005) investigated how zooid densities in a colony of the upright bifoliate species Pentapora foliacea related to stable oxygen isotope data gathered during a previous investigation by Pätzold et al (1987). The study dem onstrated covariation between zooid density and contemporaneous δ…”
Section: Growth In the Fieldmentioning
confidence: 99%